Textbook of Refractive Laser Assisted Cataract Surgery (ReLACS) - Krueger, Ronald R.; Talamo, Jonathan H.; Lindstrom, Richard L. (Springer New York : Imprint: Springer, 2013)
Textbook of Refractive Laser Assisted Cataract Surgery (ReLACS) is a comprehensive reference for the general ophthalmologist and cataract surgeon regarding the explosive new technology in femtosecond laser cataract surgery.  Femtosecond laser allows extreme precision in surgery, and is used in refractive surgery and for 'cuts' in the cornea, leading to a more uniform treatment for the patient. Textbook of Refractive Laser Assisted Cataract Surgery (ReLACS) is for cataract surgeons and all eye care providers managing or diagnosing cataracts who wish to be informed about this technology and its applications.  Edited and written by recognized leaders in the field, this book covers background, technical, clinical, and commercial aspects of this exciting technology. Some of the topics covered include the evolution of cataract surgery, femtosecond laser fundamentals, challenges of femtosecond laser technology for cataract surgery, and the economics of laser cataract surgery.  .